PKM : Pelatihan Inovasi Produk Kripik Emping Kota Cirebon - Willy Prihartono; Ade Irma Purnamasari; Agus Bahtiar; Richardus Sakarias Berek; Niko Ramadhan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
In an effort to enhance the quality and competitiveness of emping chips in Cirebon City, this Community Service Program (PKM) focuses on product innovation training. Introduction: Cirebon City is renowned for its emping chips, a regional specialty. However, the primary challenge lies in the lack of innovation in flavor variety and packaging, making it difficult for these products to compete in broader markets. The aim of this activity is to provide knowledge and skills to emping chip entrepreneurs to create innovative product variants and improve packaging quality to be more appealing to consumers. Methods: The implementation methods include organizing workshops and practical training covering techniques for flavor innovation, the use of safe additional ingredients, and modern packaging strategies. Additionally, participants received material on digital marketing strategies to expand market reach. Results: The results of this activity indicate a significant improvement in participants' abilities to create new flavored emping chips and more attractive packaging. Participants also started utilizing digital platforms to promote and sell their products, directly impacting increased sales and market penetration. This program successfully delivered positive impacts on the local economy and enhanced the competitiveness of Cirebon City's emping chips.